2005
DOI: 10.1080/09637480500103946
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of yellow mosaic geminiviral disease on bitter gourd (Momordica charantia) and its impact on phytochemical contents

Abstract: Natural occurrence of yellow mosaic disease was observed on bitter gourd (Momordica charantia). Association of geminivirus with the disease was investigated through polymerase chain reaction using geminivirus-specific primers and Southern hybridization with a probe prepared from the cloned DNA of a known geminivirus. The fruits, leaves and stem of infected and healthy plants were studied for phytochemical composition. The amounts of protein were 49%, 50% and 66% higher, total carotenoids were 36%, 33% and 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 12 publications
4
12
0
Order By: Relevance
“…Similar observations were reported for begomovirus-infected bitter gourd, where the total level of proteins was increased from 49 to 66 % (Raj et al 2005). Content of vitamin C declined by 25 % and antioxidants level declined by 35–47 % in infected leaves and fruits.…”
Section: Discussionsupporting
confidence: 85%
“…Similar observations were reported for begomovirus-infected bitter gourd, where the total level of proteins was increased from 49 to 66 % (Raj et al 2005). Content of vitamin C declined by 25 % and antioxidants level declined by 35–47 % in infected leaves and fruits.…”
Section: Discussionsupporting
confidence: 85%
“…According to Srivastava et al (2010) plant viruses inhibit the production of chlorophyll and other plant based pigments. Specifically, viruses that cause yellowing or discolouration of leaves lead to destruction of the chlorophyll pigments, in addition to loss in leaf nutrient content (Raj et al, 2005). Thus, as observed in this study, the most likely explanation would be viral destruction of photosynthetic apparatus in the fully developed leaves.…”
Section: Leaf Pigment Contentsmentioning
confidence: 73%
“…From the literatures, BM is known to contain compounds such as momorcharins, momordenol, momordicilin, momordicins, momordicinin, momordin, momordolol, charantin, charine, cryptoxanthin, cucurbitins, cucurbitacins, cucurbitanes, cycloartenols, diosgenin, elaeostearic acids, erythrodiol, galacturonic acids, gentisic acid, goyaglycosides and goyasaponins (Grover & Yadav, 2004), caffeic acid and ferulic acid (Raj, Khan, Singh, Kumari, & Prakash, 2005), fisetin and isorhamnetin (Lako et al, 2007), 3b,25-dihydroxy-7b-methoxycucurbita-5,23(E)-diene, 3b-hydroxy-7,25-dimethoxycucurbita-5,23(E)-diene and 3-O-b-D-allopyranosyl-7b,25-dihydroxycucurbita-5,23(E)-dien-19-al (Harinantenaina et al, 2006). Its MAP30 protein exhibited anti-HIV and anti-tumor activities (Lee- Huang et al, 1995), momorcharins and momordins showed activities in inactivating ribosomes, momordin 1c and oleanolic acid glycoside in altering gastrointestinal transit time and blood glucose (Chao & Huang, 2003;Grover & Yadav, 2004).…”
Section: Introductionmentioning
confidence: 99%